Organization of regular passenger transportation taken into account of citizens’ appeals and dispatch control - L. S. Trofimova; D. V. Gavrilin; A. S. Kabzhamitova (Вестник СибАДИ)
Introduction. The relevance of the research performed is justified by the role of organizing passenger transportation to fulfill the terms of the ‘Municipal contracts for the performance of work related to the regular transportation of passengers and luggage by buses at regulated tariffs’ (hereinafter referred to as the Contract). The unevenness of passenger flows associated with the changing nature of the movement of people and the influence of a combination of probabilistic factors leads to a deviation of the planned indicators of the Contract from the actual ones. The purpose of this study is to establish the relationship between the functioning of the Incident Management system and dispatch control of municipal passenger enterprises to fulfill the terms of the Contract when organizing regular passenger transportation on municipal routes.Materials and methods. This study applies generally accepted methods from the theory of passenger road transport. When achieving the goal, the sequence of information processing in the Incident Management system, Dispatcher and Maps software modules was taken into account. The practical implementation of the research results using the example of a municipal route in the city of Omsk was carried out.Results. A classification of citizens’ appeals according to which incidents related to the organization of passenger transportation include appeals related to changes in bus performance indicators established by the Contract is proposed. To generate information using dispatch control of municipal passenger enterprises, it is proposed to use an automated navigation system for dispatch control. A model of the relationship between the functioning of the Incident Management system and dispatch control of municipal passenger enterprises has been developed for the organization of regular passenger transportation on municipal routes.Conclusion. The established relationship between the functioning of the Incident Management system and dispatch control of municipal passenger enterprises is recommended for organizing regular passenger transportation on municipal route № 24 in the city of Omsk.